Marketing Strategy for Modern Chicken Broiler (Study Case : CV. Berdikari Putra Abadi) - Narimo, Sabar; Nuha, Amatullah Ashshobriatu; Dzulfiqar, Helmi Aufa; Setiawan, Hendi (Proceedings International Conference on Education Innovation and Social Science, 2022)
This research aims to (1) identify the company's internal and external factors in marketing modern broiler products (2) Formulate strategies that can be carried out by companies to increase marketing of modern broiler products in the market regarding product, price, promotion and distribution, (3) Recommend the best strategy from a variety of alternative strategies that can be formulated. This research used qualitative method with a case study research design. The subject is CV. Berdikari Putra Abadi which located in Grogol, Sukoharjo, Indonesia. While the object is modern broiler products. Data collection techniques were conducted through interviews, observation, participatory and documentation, while the analysis technique uses mile and huberman data reduction, data display, and conclusion drawing. The result formulation of an alternative marketing strategy that is obtained based on external and internal factors by entering into a cooperation contract for the distribution of modern broiler and offering custom chicken meat. Based on the results of the SWOT analysis, it was found that the promotion of custom chicken meat is the main recommended priority strategy.